El distanciamiento brechtiano en el teatro de Santiago García (1960-1990) - Aldana Cedeño, Janneth (Latin American Theatre Review, 2018)
The greatest part of Santiago García’s artistic creation and, by extension, of the group Teatro La Candelaria under his direction, has been done through the sustained effort to generate an art devoted to contemporary social transformations, simultaneously committed to the critical judgment of the potential spectators. Bertolt Brecht’s contributions, particularly his theorizing on the “detachment effect,” have been instrumental to artists in establishing effective communication with those sectors of society that do not have access to certain cultural goods but desire to change their difficult living conditions.